Perception of IT teachers on their methodological development: A case at Kazakhstan universities - Mukhatayev, Aidos; Omirbayev, Serik; Kassenov, Khanat; Biloshchytskyi, Andrii; Omarova, Safura (International Journal of Innovative Research and Scientific Studies, 2024)
This paper provides an analysis of the viewpoints of IT discipline teachers at Kazakhstani universities regarding the need for the development of methodological competence. The purpose of this study is to provide IT teachers with a philosophy of necessity to develop their methodological basis to train future IT specialists. The sociological survey was conducted among them and the answers to the questionnaire showed that teachers understand the relationship between their methodological training and the quality of education. The interviewed teachers use a variety of technologies and methods of teaching and evaluating the achievement of learning outcomes by students in the educational process which indicates that they have a certain level of methodological competence. Nevertheless, the problem of unclear understanding of the differences between the concepts of technology and teaching method is revealed. This suggests the need for measures to strengthen the general pedagogical training of teachers. The study’s findings have shown that IT discipline teachers at Kazakhstani universities understand the need for constant development of their methodological competence. The opinion of teachers in the IT discipline about the need to develop methodological competence is positive and they are ready for continuous improvement. The study gives a foundation for research on the level of formation of methodological competence in general and its components, organizational forms of development of methodological competence and the possibility of strengthening the general pedagogical training of future teachers of IT disciplines.